Fire performance of cold-formed steel shear wall with different steel grade and thicknesses. (February 2021) - Samiee, Parisa; Esmaeili Niari, Shirin; Ghandi, Elham
Abstract: In recent years the use of light gauge steel structures made of cold-formed steel has grown substantially around the world due to its unique advantages such as its cost effectiveness, durability, light weight and ease of use. Cold-formed steel sections have high section factor and high thermal conductivity, which result in a rapid increase in temperature during the fire, and under fire condition these sections experience a rapid reduction in strength and stiffness, thus investigating the behavior of these structures under fire has become particularly important. This paper presents the numerical study of behavior of cold-formed steel shear wall under fire condition. At first the finite element model of cold-formed steel shear wall was developed using Abaqus software and then the thermal and structural analysis were carried out taking into account the effects of geometric and material nonlinearities. To confirm the validity of numerical model, the results of the numerical model are compared with the previous test results. Further parametric studies have been carried out by considering some of the parameters affecting the behavior of cold-formed steel shear wall against fire such as the grade of steel and the thickness of cross section. The results of thermal analysis presented in the form of time–temperature profiles of hot flange, cold flange and web of stud, show that increasing the thickness of steel can lead to a decrease in the temperature of steel sections which is more evident in hot flange. Structural analysis of wall under fire condition have been studied under two conditions, namely steady and transient state conditions. In this analysis the effect of steel grade and thickness have been investigated separately. The results of structural analysis at room temperature are presented as axial force–displacement diagrams and failure modes, which show that increasing the thickness and grade of steel leads to an increase in ultimate compression capacity of stud. The results also show that increasing the stud thickness to a certain amount (1.55 mm) leads to an increase in fire resisting rating (FRR) and the use of high strength steel in load ratio range of 0.3–0.7 result in an increase in FRR.